Pengaruh Kualitas Pelayanan, Price Fairness dan Promosi terhadap Kepuasan Konsumen pada The Beach Restaurant di Kabupaten Badung - Murtini, Ni Putu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The purpose of this study was to find out how service quality, price and sales promotion affect customer satisfaction at The Beach Restaurant in Badung Regency. This research was conducted at The Beach Restaurant, Badung Regency on Jalan Camplung Tanduk No. 66 Seminyak, Bali. The population in this study are all consumers who come to The Beach Restaurant to shop. Population, one invoice is assumed to be the same as one consumer who comes to shop at The Beach Restaurant in Badung Regency, it is concluded that the total population is 9,235 people. The sample for this study was 99 out of 9,235 consumers at The Beach Restaurant in Badung Regency. The Slovin formula is used as an example of a calculation method. Based on the results of these calculations, the number of samples determined in this study is rounded up to 99 consumers at The Beach Restaurant. The data analysis technique used is multiple linear regression analysis. Based on the results of data analysis where service quality has a positive and significant effect on customer satisfaction. Price fairness has a positive and significant effect on consumer satisfaction. Promotion has a positive and significant effect on consumer satisfaction. Service quality, price fairness and promotions simultaneously have a positive and significant effect on customer satisfaction.